Anisotropy of Structure and Strength Properties of High-Temperature Cu-Cr-Zr Composite, Induced by Equal-Channel Angular Pressing - A.I. Belyaeva; A.A. Galuza; I.V. Kolenov; S.N. Faizova; G.I. Raab; I.A. Faizov (Журнал нано- та електронної фізики)
In the paper influence of thermal treatment and equal-channel angular pressing (ECAP) on properties of high-temperature Cu-Cr-Zr composite is studied. It is shown, that proper combination of these two treatments leads to increase of the alloy microhardness while preserving high electroconductivity. It is proved experimentally, that structure formation of Cr-rich precipitates is not connected with the size of the matrix structural elements which is close to the size of the precipitates. High ECAP-induced anisotropy of both structure and spatial arrangement of Cr-rich fibers along and across the sample axis, and of the composite microhardness is revealed. It is shown, that ECAP results in anisotropic strengthening of the composite due to anisotropic distribution of Cr-rich precipitates. Conductivity remains rather high and isotropic since it is determined by the isotropic matrix properties.